Smart Tourism: between technology, participation and sustainability - Ercole, Enrico (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
Smart Tourism: between technology, participation and sustainability. The article deals with smart tourism, understood as the relationship between tourism, and technology, participation and sustainability. The macro approach adopted allows to approach the object of study from various points of view and to relate broad and complex issues, whose relations with tourism are usually treated separately. However, this advantage is accompanied by the limit of dealing with the issues, by force of circumstances, in general. The innovativeness of the article lies in the type of approach, which highlights the potential, but also the ambiguities and critical issues related to smart tourism, a fuzzy concept and a fashionable buzzword. The first section outlines the transformation of tourism within the broader transformation of the social system and subsystems: economic, political, value. The following sections deal with the relationship between smart tourism and the three subjects under study: technology, participation, sustainability. The conclusions reflect on the criticalities of the concept of smart tourism and outline future lines of research.